Social Dynamics on the Increasing Divorce of Malay Communities during COVID-19 in Sambas West Kalimantan, Indonesia Perspective of Islamic Family Law - Asman, Asman; Muda, Resali bin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
The purpose of this study is to find out the causes and provide alternative solutions to the increase in divorce of the Malay community in Sambas Regency, West Kalimantan. The emergence of Covid-19 at the beginning of 2019 as a very scary and deadly virus for mankind in this world. One of them is Indonesia, which has been greatly affected by Covid-19, both from the family economy side and from the family resilience side. One of the cases that occurred in Sambas Regency was that in 2021 there was an increase in divorce during the Covid-19 pandemic, resulting in a change in status. This type of research is a type of qualitative research that prioritizes field studies with a normative juridical approach. The focus in this research is what causes the increasing divorce status of the Malay community during the Covid-19 period in Sambas Regency? And what are the alternative solutions to reduce the high divorce rate during the Covid-19 period in Sambas Regency. The findings of this study are the increase in divorce in Sambas Regency, the existence of conflicts in the families of married couples which results in divorce the main cause of problems in life or family economic resilience, communication in the family is tenuous and marriage. immaturity is caused by being too young to start a household. The alternative solution provided by this study is that husband and wife must communicate actively without prioritizing 2E, namely emotion and egoism to avoid conflict, synergistic active intervention from religious leaders, government, KUA, BBKN and families, to conduct socialization in order to create good relationships for newly married couple or husband and wife who have been married for a long time